Numerical investigation of heat transfer in structured rough microchannels subjected to pulsed flow. (October 2021) - Singh, Shashank; Singh, Siddhartha Kumar; Mali, Harlal Singh; Dayal, Ram
Highlights: Comparison of pulsed flow against continuous flow for microchannel heat transfer. 32.76 Optimum pulse frequency independent of wall roughness. Channel hydraulic diameter has greater impact than wall roughness on heat transfer. Abstract: Heat sinks are popular devices for cooling of electronic components, and their performance can be enhanced by flowing a cooling fluid through micro-scale channels. While previous works concentrated on continuous flow of coolant through channels, in this work effect of pulsed flow through microchannels is studied. Further, the effect of structured wall surface roughness is also considered. Full factorial experiments are designed with channel hydraulic diameter and wall roughness as parameters with 3 levels each and 2D simulations are performed for all cases. Initial comparison indicates better performance in pulsed flow against continuous with a maximum enhancement of 32.76% in average Nusselt number. Unlike continuous flow, pulsed flow is found to create vortices in fluid irrespective of wall roughness which enhances heat transfer. Optimum pulse frequency is found to vary with hydraulic diameter but is independent of wall roughness. Wall roughness is found to assist heat transfer for all channels however with a pressure drop penalty. Maximum increment of 29.29% in average Nusselt number due to wall roughness is observed for hydraulic diameter of 300 μm, when roughness is increased from 0 to 50 μm. Increasing hydraulic diameter is found to be detrimental to heat transfer and a maximum reduction of 29.10% in average Nusselt number is observed on increasing diameter from 300 to 700 μm at constant wall roughness. Based on the results, a pulsating flow may be adopted for microchannel based electronic liquid cooling systems.